Flexible Laryngoscopy Audit in Outpatient Department of a tertiary care hospital, Islamabad - Mumtaz Ahmad Umar, Mohibullah Mushwani, Naveed Arshad (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Flexible laryngoscopy is less operator/patient dependent diagnostic procedure with magnified field and well tolerated diagnostic procedure. Flexible laryngoscopy is tolerable diagnostic procedure with clear and magnified visualization of interior larynx. Aim: To audit the flexible laryngoscope in outpatient department in our local setting. Methods: A retrospective audit survey was carried out in Outpatient ENT Department of Akbar Niazi Teaching Hospital, Islamabad between June 2021 and May 2022. Total 85 patients with age range 10-80 years, with history of laryngopharyngeal symptoms and preoperative evaluation of thyroidectomy patients were selected. After getting detail history of flexible naso-pharyngo-laryngoscopy and findings were documented and analyzed. Under local anesthesia, spray in the nose and throat gargles. The laryngoscope passed through nose and nasopharynx into the laryngopharynx, and assessing all the structures. Data was analyzed through SPSS v 22. Results: The patients mean age was 28.96±9.14 years. Among all the patients 49(57.64%) were female and 36(42.3%) were male. The population highest percentage 26(30.5%) were 21-30 years old. The laryngeal complaint of hoarseness was highest with 38.8% indicated after flexible laryngoscope procedure according to other symptoms. According to diagnosis made on flexible laryngoscopy, the vocal nodules were highest with 15.3% detected. The diagnostic tools in diagnosis of laryngeal pathologies, its availability and cost effectiveness led to limited access of the patients to such sophisticated diagnostic procedure. Conclusion: Flexible laryngoscopy gives detailed visualization of the larynx and don’t leave the examiner inconclusive about laryngeal pathologies. Keywords: Clinical audit; Diagnostic equipment; Laryngoscopy; Nasopharyngeal diseases; Outpatient clinics, hospital.